Acetylcholine from tuft cells promotes M2 macrophages polarization in Hirschsprung-associated enterocolitis - Zheng, Ziyi; Lin, Lin; Lin, Huifang; Zhou, Jie; Wang, Zhe; Wang, Yang; Chen, Jianxin; Lai, Caimin; Li, Renfu; Shen, Zhiyong; Zhong, Ming; Xie, Cheng; et al. (Frontiers in Immunology, 2025)
BackgroundHirschsprung-associated enterocolitis (HAEC) is one of the most severe complications in patients with Hirschsprung’s disease (HSCR). Previous research has indicated that acetylcholine (ACH) plays an anti-inflammatory role during inflammation by acting on the α7 nicotinic acetylcholine receptor(α7nAchR) to promote the secretion of anti-inflammatory factors. However, the specific role of ACH in HAEC remains unclear. This experiment aims to explore the sources of ACH in HSCR and its anti-inflammatory mechanisms, thereby identifying new directions for the prevention and treatment of HAEC.MethodsWe analyzed single-cell transcriptome data from HSCR to identify cells that secrete ACH and observed their distribution using immunofluorescence. In Ednrb-/- mice, F4/80, iNOS, ARG-1 and CD206 were used to identify and locate M1 and M2 macrophages in different intestinal segments. Western blot, reverse transcription-quantitative polymerase chain reaction, and enzyme-linked immunosorbent assay were used to test the levels of IκBα, tumor necrosis factor-α, interleukin-10, and the macrophage activation pathway proteins JAK2 and STAT3 in different intestinal segments of Ednrb-/- mice. Organoid and cell culture techniques were used to verify the anti-inflammatory mechanism of ACH in vitro models.ResultsscRNA-seq analysis revealed that tuft cells expressed the CHAT protein. In HSCR, aganglionic segments exhibited heightened cholinergic activity compared with dilated ganglionic segments. In HAEC, inflammation was mainly concentrated in the dilated ganglionic segment and was associated with an increase in M1 macrophages, whereas the aganglionic segment showed less inflammation and was associated with an increase in M2 macrophages. Furthermore, in vitro experiments showed that intestinal organoids containing tuft cells promoted an increase in M2 macrophage markers, and ACH promoted M2 macrophage polarization.ConclusionsDifferences in inflammation among various intestinal segments in HAEC may be linked to ACH secreted by tuft cells. Drugs targeting tuft cells have the potential to become important components of HAEC treatment in the future.